The Inauguration of Faisal Bin Al -husain as Iraq King (A Study of British Documents) (Journal of the College of Education for Women, 2019)
Husain as a king of Iraq.This paper deals with the British communication with faisel . then Winston Churchill's speech in British common house .then fodlowed by arriving faisal to Iraq after that the referend um faisel .The his claims of British maneuver lastly coronation on faisal & his inauguration as a king of Iraq.